Penyuluhan Partisipatif untuk Meningkatkan Adopsi Sistem Jajar Legowo - Rizal Akbar; Widya Hasian Situmeang; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research program aimed to improve farmers’ understanding of the Jajar Legowo rice planting system and to analyze the factors influencing their perceptions. The program was conducted with the Sukatani Farmer Group in Tukdana Village, Indramayu Regency, using a mixed-method approach that combined observation, interviews, and questionnaires with 30 farmers. The results showed that farmers’ knowledge of the Jajar Legowo system was relatively low (54.17%), while their attitude was in the moderate category (58.92%). Correlation analysis revealed a strong relationship between knowledge and attitude (r = 0.672), which together shaped farmers’ perceptions of the system. Further analysis indicated that only land area had a significant influence on farmers’ perceptions, while age and education level showed no significant effect. Qualitative findings also revealed that farmers’ perceptions were influenced by direct farming experience, agricultural extension activities, institutional support, and social influence from leading farmers. Based on these findings, efforts to increase the adoption of the Jajar Legowo planting system require participatory extension strategies, hands-on demonstrations, and strengthened farmer group involvement.